Non-volant mammals in the central Andes Yungas: the Pampa Hermosa National Sanctuary - Cervantes, Klauss; Arias, Edith; Aguilar, Adela; Larico, César; Pacheco, Víctor (THERYA, 2024)
The Pampa Hermosa National Sanctuary (SNPH) is a Natural Protected Area (11,543 ha) that encompasses a large extension of central Yungas; however, despite its high priority status for the conservation of biodiversity, the non-volant mammals have been poorly documented. This study reports the non-volant mammals from the Yungas of the SNPH and its buffer zone, for the first time. We sampled four localities: Podocarpus (1,900 m), Los Cedros (1,600 m), Santa Isabel (1,450 m), and Nueva Italia (1,370 m), which encompass very humid premontane and montane forests. We used capture methods for small mammals; and direct and indirect records for medium and large-sized mammals. The capture effort was 6,860 traps-night (Sherman and Victor traps) and 490 buckets-night (pitfall traps). We recorded 31 native species: six marsupials, one cingulate, two primates, 18 rodents, two carnivores, and two artiodactyls, including the threatened species Lagothrix lagotricha tschudii and two endemic rodents. The most diverse orders were rodents and marsupials (77 %). The analysis of true diversity (qD) showed that the montane forests of SNPH (1,600 to 1,900 m) had the highest values: Los Cedros (0D = 18.80) when order q = 0; and Podocarpus (1D = 6.34; 2D = 4.99) when order q = 1, 2. The rank-abundance curves indicated the same taxa group (Hylaeamys yunganus, Akodon cf. A. aerosus, and species of Neacomys) as the most abundant at all localities. The species Marmosa (Micoureus) constantiae, Hylaeamys yunganus, Rhipidomys gardneri, Euryoryzomys nitidus, Oligoryzomys microtis, and Neacomys macedoruizi are the first records for the region of Junín. One species of Neacomys and another of Oecomys might be new species to science. A beta diversity analysis showed that the Yungas of SNPH are more similar to the Manu National Park (21 %) and the Tingo María National Park (20 %); highlighting that dissimilarity is high even between relatively close communities. Our study indicates that the SNPH allow connectivity with other nearby Yungas, especially for medium and large-sized mammals that need pristine and preserved forests. Nevertheless, the real diversity of the region is still far from being completely inventoried; additional evaluations with a diverse array of methods are needed toward that goal. In addition, the local and regional governments should get involved in conserving these fragile forests where the changes in land use may affect many key and endemic species.